Ay, bayot! my husband's lover and the inclusion of the LGBTQIA+ members in the infidelity discourse as received by Cebuano Young Professionals - Cadiz, Reyna C.; Gamboa, Joanah N. (College of Communication, Art, adn Design, University of the Philippines Cebu, 2018)
Abstract: Television is still the leading communication medium in the country, notwithstanding the fast emergence of the Internet and other multimedia technologies. Its representations on various themes such as love, family, triumphs and struggles (through teleseryes) have become a prominent source of cultural texts and played a significant role in the social construction of the Filipino reality. Like all other teleseryes, Philipine kabitseryes (soap operas that revolve around infidelity) have preserved the heteronormative discourse perpetuated by the patriarchal system. However, GMA 7?s My Husband Lover (2013) deviated from the conventional narrative on infidelity and included LGBTQIA+ members in the discourse. By conducting a reception analysis through textual analysis anchored on Stuart Hall's Encoding-Decoding Model, the study revealed that Cebuano Young Professionals positively receive My Husband's Lover and the ideologies it presented. Infidelity still remains to be a heteronormative discussion by default, but the participants acknowledge the existence of homosexual infidelities in this discourse. The Cebuano YPs' articulations and meaning-making reflected their resistance to patriarchy and heteronormativity that dictate an individual's performativities. Results further show the YPs' readiness to support the proliferation of shows with queer narratives.